Comb-assisted cavity ring down spectroscopy of 17O enriched water between 7443 and 7921 cm-1 - Modelain D.; Mikhailenko S. N. Semen Nikolaevich; Karlovets E. V.; Beguer S.; Kassi S.; Campargue A. (2017, 2017)
Title screen